Management challenges of an early education center at a federal university - Rassele Soprani, Maria José; Moreira Dutra Filho, João; Fernandes Palmeira, Andressa; Corrêa da Silva, Marina (Guará Journal, 2016)
This is a review article which aims to address the management of an Early Childhood Education Center of a Public University in Brazil. Some management challenges of this Early Childhood Education Center will be discussed, such as, administrative public servant performing teaching tasks, as well as the importance of the school democratization process seen in many aspects such as the election of school principals which represents an improvement on the social democratization scenario experienced by public school. This article was supported in theoretical research based on the literature focusing on the public school management, and in a historical documentary research about the early childhood education center of the Federal University of Espírito Santo. The legal basis will be subsidized by the analysis of some articles of the Constitution of the Federative Republic of Brazil (1988), some specific Education Laws, among others